Expression of Dual-Specificity Phosphatase 9 in Placenta and Its Relationship with Gestational Diabetes Mellitus - Qiang Wei; Xiaomin Pu; Li Zhang; Yi Xu; Meifan Duan; Yuemei Wang (Journal of Diabetes Research)
Introduction. The aim of the present study was to examine placental levels of DUSP9 mRNA and protein and to investigate the potential role of DUSP9 in the development of gestational diabetes mellitus (GDM). Methods. Placental tissues from pregnant women with GDM (n=17) and normal healthy pregnant women (n=16) were collected at delivery. The expression of DUSP9 mRNA in placental tissue was analyzed by real-time PCR, while the expression of DUPS9 protein was evaluated by immunohistochemistry and western blot. Differences in the expression levels of DUSP9 mRNA and protein between the two groups were assessed, as well as potential correlations between DUSP9 mRNA expression levels and relevant clinical indicators. Results. Blood glucose levels were significantly higher in the GDM group than in the control group, based on an oral glucose tolerance test. DUSP9 protein was expressed in the placental cytotrophoblasts in both groups, and placental levels of DUSP9 protein and mRNA were significantly higher in women with GDM. Placental DUSP9 mRNA levels in all 33 women correlated moderately with delivery gestational week (R=0.465, P=0.006), fasting plasma glucose (R=0.350, P=0.046), 1-hour postload plasma glucose (R=0.363, P = 0.038), and 2-hour postload plasma glucose (R=0.366, P=0.036), but not with maternal age, preconception body mass index, prenatal body mass index, or neonatal birth weight. Multiple linear regression analysis indicated that delivery gestational week was an influence factor of DUSP9 mRNA levels (β1=0.026, P<0.05). Conclusions. DUSP9 upregulation in the placenta of GDM pregnant women may promote insulin resistance, which may correlate with the occurrence of GDM. But there is still possibility that DUSP9 upregulation was the results of insulin resistance and/or hyperglycemia. Further research is needed to explore the role of DUSP9 in GDM.